2019
DOI: 10.3390/sym11121469
|View full text |Cite
|
Sign up to set email alerts
|

An Equivalent Damping Numerical Prediction Method for the Ring Damper Used in Gears under Axial Vibration

Abstract: In aircraft gas turbine engines, gears in the transmission system are typically cyclic in structure and inevitably encounter large dynamic loads, such as meshing excitation, resulting in high vibration loads in resonance. To prevent gear resonance failure, a ring damper is employed to reduce the resonance response. As relative motion between the gear and the ring damper occurs, vibration loads can be reduced by friction energy dissipation. Moreover, the gears in the aircraft engine are thin-walled and their ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…At the same time, the mass and length of the spacecraft remained unchanged. In these figures, the solid blue line also shows the change in the average value of the angle of attack, obtained from the numerical solution of Equation (12). At the same time, in Figures 5-7, in the form of a solid red line, the change in the actual value of the amplitude of the angle of attack, obtained from the numerical solution of Equations ( 10) and (11), is also shown.…”
Section: Numerical Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…At the same time, the mass and length of the spacecraft remained unchanged. In these figures, the solid blue line also shows the change in the average value of the angle of attack, obtained from the numerical solution of Equation (12). At the same time, in Figures 5-7, in the form of a solid red line, the change in the actual value of the amplitude of the angle of attack, obtained from the numerical solution of Equations ( 10) and (11), is also shown.…”
Section: Numerical Resultsmentioning
confidence: 76%
“…Figures 2-4 show characteristic numerical results demonstrating the nonlinear monotonic stability of the average oscillation amplitude, obtained when the condition f '1 > 0 is true. In these figures, the blue line shows the change in the value of the average value of the angle of attack, obtained from the numerical solution of Equation (12). In this case, Figures 2-4 in the form of a solid red line show the change in the actual value of the amplitude of the angle of attack, obtained from the numerical solution of Equations ( 10) and (11).…”
Section: Numerical Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The approaches have been founded based on the aerodynamic component division into mass, damping, and stiffness matrices which can be added to structural components. The distribution of mass and stiffness of the structure have a direct effect on the speed and frequency of the Aerial vehicle, and consequently, its flutter [18,19]. It can be concluded that the presence of any structural component with a significant mass and stiffness relative to the mass and stiffness of the main structure can affect the speed and frequency of the flutter (e.g., tank, landing gear, and control surfaces such as an aileron).…”
Section: Introductionmentioning
confidence: 99%
“…They introduced the dependence of natural frequency on the change of gear shape by using simulation tools. By designing the damping ring structure, Wang [ 14 ] reduced the axial vibration of the gear and obtained the influence of the friction coefficient and mass of the damping ring on the damping characteristics. Kumar S M et al [ 15 ] improved the gear transmission efficiency by removing the gear material and found that the weight reduction method with a circular shape was more effective.…”
Section: Introductionmentioning
confidence: 99%